Writing Against Vanishing: Native American Autobiography and the Trope of an Ever-Pending Vanishment - Fabrice LE CORGUILLÉ (E-REA)
This article aims at exploring the sense of impending death that goaded Native American autobiographers in the nineteenth century; they made “colonization” rhyme with “destruction” rather than “revelation” as the etymology of “apocalypse” would suggest. Ottawa Andrew Blackbird and Omaha Francis La Flesche were both the embodiments and witnesses of what happened to Native American people. They wrote their autobiographical accounts as paradigmatic examples of the Native American tragic fate, wondering whether indigenous people were irrevocably doomed, as the dominant discourse constantly repeated, or could strive to find ways and means to adapt and survive. If not, could the hereafter represent an idealized sanctuary that nostalgic Natives would long for?